Kanalen i Tønsberg - Jan Brendalsmo; Rolf Sørensen (Collegium Medievale, 2018)
At some point during the ï¬rst half of the 1200s the Norwegian King Håkon Håkonsson organized the dredging of a canal called Skeljasteinsund through Stensarmen, an isthmus which, at the time, more or less connected the island of Nøtterøy with the mainland and the medieval town of Tønsberg. This has conventionally been thought to have been the ï¬rst time that someone decided to improve the south-easterly seaward approach to Tønsberg in this way. However, by comparing information on geology, post-glacial land rise and the necessary depth of water required to accommodate the draughts of larger vessels of the period ca. AD 800-1300, it becomes clear that already by about 800 large ships like those found at Oseberg and Gokstad have had trouble passing Stensarmen at mean sea level. It is argued that Tønsberg had a central role militarily, economically and politically during the period ca. 800 - ca. 1200 when Danish and Norwegian kings struggled for supremacy over the south-eastern part of Norway. With this in mind, it might be suggested that one or more of these kings organized the excavation of a canal during this time in order to uphold two separate access routes to Tønsberg by sea.